2012
DOI: 10.1017/s0022215112002769
|View full text |Cite
|
Sign up to set email alerts
|

Young systemic lupus erythematosus patients with no hearing involvement: 10-year follow up

Abstract: These results supply no evidence for progressive hearing loss in systemic lupus erythematosus patients with no hearing involvement at study commencement. Therefore, we recommend audiometric tests only for systemic lupus erythematosus patients complaining of hearing loss, or for other clinical purposes. It is conceivable that asymptomatic hearing loss could be observed over a more extended follow-up period (i.e. more than 10 years).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Screening by title and abstract excluded 573 articles. A full-text review of remaining studies further eliminated 18 articles, leaving a total of 17 articles 68,10,11,1728 for inclusion in the final analysis. A diagram outlining the summary of the search process is shown in Supplementary Figure S1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Screening by title and abstract excluded 573 articles. A full-text review of remaining studies further eliminated 18 articles, leaving a total of 17 articles 68,10,11,1728 for inclusion in the final analysis. A diagram outlining the summary of the search process is shown in Supplementary Figure S1.…”
Section: Resultsmentioning
confidence: 99%
“…Only studies that provided sufficient data on audiological outcomes of interest were included in the meta-analysis. Of the 17 studies, 14 studies 68,10,17,1921,2328 were used to analyze the risk of HL in patients with SLE, nine studies 6,8,11,17,19,22,24,27,28 were used to pool frequency-specific air- and bone-conduction PTT data, and two studies 8,24 were used to compare the serological and clinical profiles of patients with SLE with and without HL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Roverano et al recommended audiometric tests as part of initial studies in all SLE patients, because more than 60% of them have asymptomatic sensorineural hearing loss (6). But García‐Berrocal et al reported no evidence of progressive hearing loss in SLE patients who did not describe hearing loss at the beginning of the study; therefore, García‐Berrocal et al recommend audiometric tests only for SLE patients who describe hearing loss (7). …”
Section: Introductionmentioning
confidence: 99%